Determinants of pro-environmental innovative behaviour: A comparison of three generations - Małgorzata Baran; Barbara Sypniewska (Journal of Innovation & Knowledge)
The undeniable mutual relationship between the environment and the individual begins with the onset of human life. This human–environment relationship imposes, on every generation, the task of leaving behind a clean and sustainable environment. This study aims to investigate the determinants of pro-environmental innovative behaviours in a generational context. The study's findings provide valuable insights into the complex interplay of environmental awareness, creativity, risk-taking propensity, proactive coping and pro-environmental innovative behaviours of three generations (X, Y, Z). The results reveal substantial generational differences in the correlations between determinants such as environmental awareness, risk-taking, creativity and proactive coping. This implies that a tailored approach to encouraging innovative behaviours and environmental awareness may be required for each generation.